Long-term aerosol particle depolarization ratio measurements with HALO Photonics Doppler lidar - V. Le; H. Lobo; E. J. O'Connor; V. Vakkari; V. Vakkari (Atmospheric Measurement Techniques, 2024)
It has been demonstrated that HALO Photonics Doppler lidars (denoted HALO Doppler lidar hereafter) have the capability for retrieving the aerosol particle depolarization ratio at a wavelength of 1565 nm. For these lidars operating at such a long wavelength, the retrieval quality depends to a large degree on an accurate representation of the instrumental noise floor and the performance of the internal polarizer, whose stability has not yet been assessed for long-term operation. Here, we use 4 years of measurements at four sites in Finland to investigate the long-term performance of HALO Doppler lidars, focusing on aerosol particle depolarization ratio retrieval. The instrumental noise level, represented by noise-only signals in aerosol- and hydrometeor-free regions, shows stable performance for most instruments but clear differences between individual instruments. For all instruments, the polarizer bleed-through evaluated at liquid cloud base remains reasonably constant at approximately 1 % with a standard deviation of less than 1 %. We find these results to be sufficient for long-term aerosol particle depolarization ratio measurements and proceed to analyse the seasonal and diurnal cycles of the aerosol particle depolarization ratio in different environments in Finland, including in the Baltic Sea archipelago, a boreal forest and rural sub-arctic. To do so, we further develop the background correction method and construct an algorithm to distinguish aerosol particles from hydrometeors. The 4-year averaged aerosol particle depolarization ratio ranges from 0.07 in sub-arctic Sodankylä to 0.13 in the boreal forest in Hyytiälä. At all sites, the aerosol particle depolarization ratio is found to peak during spring and early summer, even exceeding 0.20 at the monthly-mean level, which we attribute to a substantial contribution from pollen. Overall, our observations support the long-term usage of HALO Doppler lidar depolarization ratio measurements, including detection of aerosols that may pose a safety risk for aviation.